CHANGES OF 8-OXO-2'-DEOXYGUANOSINE LEVEL IN MOUSE LIVER CELLS DNA IN CASE OF ACUTE TOXIC STRESS - N. V. Marmiy; D. S. Esipov (Тонкие химические технологии)
The changes of the 8-oxo-2'-deoxyguanosine (8-oxo-dG)/dG ratio in the DNA of laboratory mice hepatocytes under the influence of toxic stress were studied. It was shown that the injection of carbon tetrachloride causes the growth of 8-oxo-dG level. A rapid increase in the level of 8-oxo-dG in DNA occurs during the first day of the experiment at short-term toxic stress. Subsequently, 48 hours after the initial injection, the level of 8-oxo-dG decreases to the control values. This change in the value of the biomarker can be attributed to the activation of the reparative and antioxidant systems. The subsequent injection results again in an increase of 8-oxo-dG level, and the latter only increases thereafter. This reflects the exhaustion of the reparative potential of the organism and accompanies the progress of inflammation and pathological change of the liver tissue.